Effects of the explosion intensity on the distribution of flame region in a tunnel. Issue 4 (20th September 2017) - Ma, Qiuju; Chen, Jiachen; Zhang, Qi
Abstract : The purpose of present work is mainly to study the effects of explosion intensity on the distribution law of the flame region involving methane‐air explosion based on the numerical results and theoretical analysis. Numerical simulation using software package AutoReaGas, a finite‐volume computational code for fluid dynamics suitable for gas explosion and blast problems, is adopted. The simulation works were performed in a full‐scale tunnel with various wall boundary conditions so that different explosion intensity levels could be achieved. Different flame regions were achieved for the same original gas region of 56 m. The flame region is always longer than the original gas region in all cases of stoichiometric methane‐air mixtures. Higher explosion intensity can induce a shorter flame region. In the case of smooth wall, the explosion intensity is very low, so the flame region reaches up to the longest value of 218 m. The ratio between the length of flame region and the length of the original gas region ranges from 1.3 to 3.9 with the decline of explosion intensity. It indicates that even though lower explosion intensity can reduce the shock wave damage, it will enlarge the accident range and especially extend the high temperature flame hazard. © 2017 American Institute of Chemical Engineers Process Saf Prog 36: 372–377, 2017